Exploring the Potential of Gastro Retentive Drug Delivery Systems: An Insightful Perspective - Mishra, Saket; Shukla, Priyanka; Chumbhale, Deshraj Shyamkant; Dutta, Pijush; Vellingiri, Dhakshnamoorthy; Tiwari, Ruchi (International Journal of Pharmaceutical Investigation, 2025)
In today’s modern world, there is a rapid increase in the control and systemic administration of drugs through the oral route, because of its various advantages like high patient compliance, easy dose administration and availability of various formulations. One of the novel approaches in this area is Gastro Retentive Drug Delivery Systems (GRDDs) is a systemic approach to increase the gastric residence time of the drug which results in the site-specific drug release of drug in the upper part of GIT for local and systemic effect of the drug. It is a unique approach that has become more popular in the last three decades. The sole purpose of this article is to summarize and present recent as well as past article which focuses on the GRDDs and their various aspects. This article addresses briefly on various aspects of GRDDs their classification, advantages and limitations, factors affecting gastric residence time, evaluation, recent advancements, regulatory requirements and future prospective of GRDDs.
Keywords: Applications; Classification; Evaluation; Factors; Future perspectives; Method of preparation; Polymers; Recent advancements; Regulatory considerations